1996
DOI: 10.1183/09031936.96.09030472
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygenation upregulates rat lung Na,K-ATPase

Abstract: H Hy yp pe er rb ba ar ri ic c o ox xy yg ge en na at ti io on n u up pr re eg gu ul la at te es s r ra at t l lu un ng g N Na a, ,K K--A AT TP Pa as se e In the present study, we tested whether short-term HBO, prior to inducing lung injury, would upregulate lung Na,K-ATPase.The results show that HBO, either intermittent or single 2.5 h exposure, increased lung Na,K-ATPase α-1 and β-1 messenger ribonucleic acid (mRNA) transcript levels up to fourfold. Na,K-ATPase activity in lungs of rats exposed to HBO increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…It is well established that oxidant-induced lung injury results in damage of the alveolar capillary barrier causing capillary leak and lung edema accumulation. Previous studies show that this process results in upregulation of pulmonary Na,K-ATPase as a part of the protective mechanism against reactive oxygen species [12][13][14][15]. Our results are consistent with these findings showing a hyperoxic-induced lung edema formation and increased nonselective permeability of alveolar epithelium as well as upregulation of Na,KATPase gene expression.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It is well established that oxidant-induced lung injury results in damage of the alveolar capillary barrier causing capillary leak and lung edema accumulation. Previous studies show that this process results in upregulation of pulmonary Na,K-ATPase as a part of the protective mechanism against reactive oxygen species [12][13][14][15]. Our results are consistent with these findings showing a hyperoxic-induced lung edema formation and increased nonselective permeability of alveolar epithelium as well as upregulation of Na,KATPase gene expression.…”
Section: Discussionsupporting
confidence: 82%
“…These events may lead to upregulation of pulmonary Na,K-ATPase and increase sodium clearance across the alveolar epithelium as a part of the protective mechanism against reactive oxygen species generated during hyperoxia [12][13][14][15]. In some cases reactive oxygen species, such as super oxide anion, hydroxyl radical and hydrogen peroxide, may be generated at a rate that overwhelms the natural defenses of the cell leading to destructive oxidation [16].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure of rats to sublethal hyperoxia (85% O 2 ) increased alveolar type II cell ␣-rENaC mRNA level (387). In addition, it has been recently reported that ␣ 1 -and ␤ 1 -Na ϩ -K ϩ -ATPase mRNA subunit levels both increased in alveolar type II cells from rats exposed to hyperoxia (148). The mechanism whereby O 2 tension regulates sodium channels and Na ϩ -K ϩ -ATPase gene expression is thought to be transcriptional.…”
Section: B Hypoxiamentioning
confidence: 99%
“…Transcription factors are also involved in sodium pump gene regulation as was observed in renal cells undergoing hypoxia where ␤ 1 transcription was enhanced by the binding of SP1/SP3 near the promoter region of ␤ 1 (25,26). The up-or downregulation of sodium pump expression and activity plays a role in preventing the exacerbation of some diseases as is the case during hyperbaric oxygenation of the lung where increased ␣ 1 and ␤ 1 subunit levels help to prevent pulmonary edema (27). In renal carcinoma-like cells, the increased expression of heterologous sodium pump ␤ 1 subunits reduces cell motility and invasiveness by forming intercellular interactions between adjacent ␤ subunits (28,29).…”
mentioning
confidence: 99%